Legal Effects on PPAT That are Involved in the Making of Multiple Certificates - Kasanda, Helend; Adjie, Habib (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2022)
In the implementation of maintaining and protecting the rights of citizens and providing clear legal certainty regarding the registration of a plot of land in order to legalize ownership of land parcels and individual rights in control over land on the basis of PP no. 24 of 1997 concerning Land Registration. PPAT is a public official who is authorized to make a deed of transfer of land rights, deed of assignment of land rights, and deed of power of attorney to impose Mortgage Rights. With this authority, PPAT can take other people’s rights by making land deeds for the issuance of other certificates on land owned by other people, so there will be multiple certificates on the same piece of land. In his behavior that violates and abuses his authority and obligations as PPAT, the legal impact of dishonorable dismissal or criminal threats needs to be carried out in order to protect the rights of land owners from crimes committed by PPAT that can harm other parties.